The Effect of Motivation, Communication and Work Stress on Employee Job Satisfaction of Pt. Mitra Pangan Nusantara, Jakarta - Nur Bandarulloh; Maria Josefa Fabiana Esomar (Maneggio, 2024)
Employees are human beings with ways of thinking, feelings, and willingness that outwardly affect behavior towards work, which includes Motivation, Communication and Stress. In a company, the most concerned thing is employee job satisfaction, this is with the aim of increasing the productivity of the performance that has been provided through employees to the company. The samples used are Random Sampling as many as 150 respondents. Thus, the population used is 110 respondents who come from all employees working at PT. Mitra Pangan Nusantara. Data obtained from questionnaires distributed to employees using testing techniques using the Application SPSS version 25. The results were obtained that the Motivation Variable had a significant and partially positive influence on Employee Job Satisfaction. Furthermore, the Communication Variable has a negative and significant effect on Employee Job Satisfaction. Employee Job Satisfaction is positively and partly influenced by the Work Stress variable. Each of the independent variables of Communication Motivation, and Work Stress all have a positive and large influence on the dependent variables of worker satisfaction at the same time. The influence of the three variables of Motivation, Communication, and Work Stress on the Employee Job Satisfaction variable was 43.6%. Furthermore, the other 56.4% were influenced by factors outside the study.